Work Motivation, Leadership, and Work Discipline Influence on Employee Performance at PT Petronika in Gresik - Moh Umar Al Faruq; Rifki Suwaji (SEULANGA SYSTEM PUBLISHER, 2024)
Employee performance is critical to organizational success, aligning with strategic goals, customer satisfaction, and economic impact. It reflects the outcomes achieved by individuals or groups within an organization, crucial for productivity and sustainability amidst competitive environments. This study investigates the impact of work motivation, leadership, and work discipline on employee performance at PT Petronika, a Dioctyl Phthalate manufacturer that faces challenges linked to motivation, leadership, and discipline. The research aims to analyze these factors among 73 HRD employees using a quantitative approach, specifically Structural Equation Modeling (SEM). Primary data, gathered through interviews and questionnaires, is complemented by secondary data from company records and literature. Results indicate that motivation significantly enhances employee performance (p = 0.002), while work discipline also plays a crucial role (p = 0.000). However, leadership shows inconsistent impact on performance (p = 0.784), highlighting complexities in its influence. The study concludes that improving motivation and reinforcing work discipline are essential for enhancing employee performance at PT Petronika. Further research is recommended to delve deeper into the dynamics of leadership within organizational contexts.